The Nigeria Start-up Act 2022 as a Catalyst for Technological Development and Economic Growth in Nigeria (Strathmore Law Journal, 2023)
This century has heralded technological advancement in human history, particularly in Africa. The influx of technological advancement currently in play all over the world and the economic benefits that come with such advancement has necessitated the need for some regulations. Hence, stakeholders particularly, governments all over the world have made efforts to regulate and support investments in technology. These supports include laws, policies and other incentives that promote technology. Recently, the Nigerian National Assembly passed the Nigeria Start-up Act (NSA), 2022 to provide a regulatory framework for the development of start-ups as well as to provide an enabling environment for the establishment, development, growth and operation of start-ups and technology-related talents in Nigeria. The Act also seeks to position Nigeria’s start-ups ecosystem as a leading digital technology centre in Africa in terms of excellent innovators with exportable skills and capacity. It is projected that the NSA will immensely contribute to technological development for Nigerian start-up companies to compete with their counterparts at the regional and international scene. This article examines the nature of start-ups and the Nigeria Start-up Act, 2022. It further analyses the pre-enactment of the Start-up Act era in Nigeria, the emergence of the Start-up Act, the impacts the Start-up Act might have on technological development, the challenges of the Act as well as the general challenges faced by start-ups in Nigeria. The article argues that the NSA is a welcome and commendable effort for technological development and economic growth in Nigeria.